2017
DOI: 10.3390/app7121241
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Molecular Imaging of Pancreatic Cancer with a Miniature Endoscope

Abstract: It is highly desirable to develop novel approaches to improve patient survival rate of pancreatic cancer through early detection. Here, we present such an approach based on photoacoustic and fluorescence molecular imaging of pancreatic tumor using a miniature multimodal endoscope in combination with targeted multifunctional iron oxide nanoparticles (IONPs). A novel fan-shaped scanning mechanism was developed to minimize the invasiveness for endoscopic imaging of pancreatic tumors. The results show that the enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Third, fluorescent endoscopy could be carried on various cancers, e.g. gastrointestinal, [156], pancreatic, [157], gastric/stomach, [158], esophageal, [159],…”
Section: Towards Clinical Applications Of Visible and Infra-red Light Detection Methods Combined With Iron-based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, fluorescent endoscopy could be carried on various cancers, e.g. gastrointestinal, [156], pancreatic, [157], gastric/stomach, [158], esophageal, [159],…”
Section: Towards Clinical Applications Of Visible and Infra-red Light Detection Methods Combined With Iron-based Nanomaterialsmentioning
confidence: 99%
“…or kidney, [160] cancers. Combining standard endoscopic fluorescent apparatus with FIBN associated to a targeting moiety (amino-terminal fragment) could improve the quality of the fluorescence signal due to the specific tumor targeting and imaging of FIBN, [157]. In the same spirit, it was shown that the position of FIBN encapsulated in a hydrogel with upconverting materials could be adjusted via magnetic targeting to enable the fluorescent compound of FIBN to reach the desired target, hence resulting in an improved endoscopic image, [161].…”
Section: Towards Clinical Applications Of Visible and Infra-red Light Detection Methods Combined With Iron-based Nanomaterialsmentioning
confidence: 99%
“…Dai et al [53] conducted a study in which they used in vivo murine models to obtain molecular images of pancreatic tumor at transmission (forward projection) mode of PA imaging. They used multimodal endoscopic approach combined with targeted multifunctional iron oxide nanoparticles (IONPs).…”
Section: Preclinical Studies On Diagnosticsmentioning
confidence: 99%